Malawi Economic Monitor, October 2016 : Emerging Stronger - Record, Richard (World Bank, Lilongwe, Malawi, 2016)
The Malawi Economic Monitor (MEM) provides ananalysis of economic and structural developmentissues in Malawi. This edition of the MEM waspublished in October 2016. It follows on from thethree previous editions of the MEM, and is part of an ongoing series, with future editions to follow twiceper year. The aim of the publication is to foster better-informed policy analysis and debate regarding the key challenges that Malawi faces in its endeavors to achieve high rates of stable, inclusive and sustainable economic growth. The MEM consists of two parts: Part one presents areview of recent economic developments and amacroeconomic outlook. Part two focuses in greater depth on a special, selected topic relevant to Malawi’s development prospects.In this edition of the MEM, the focus of the specialtopic is on poverty and vulnerability. At a time when Malawi is experiencing a second successive year offood insecurity, the special topic focuses on the key factors that have led to persistently high povertyrates in rural areas, with these factors contributing significantly to vulnerability to the impact of climate shocks. The special topic also identifies and describes potential pathways and reforms thatcould help Malawi improve its level of resilience to better manage the impact of future shocks.